Aspectos histopatológicos da esofagite eosinofílica em crianças e adolescentes - Daud, Juliana Salomão (2017)
Introduction: Eosinophilic esophagitis (EoE) is a clinical-pathological disorder, characterized by symptoms related to esophageal dysfunction and histopathological alterations with inflammatory reactions primarily composed of eosinophils, being necessary, by the last consensus, 15 or more eosinófilos / high-power field (hpf). However, this histopathological finding is usually accompanied by other morphological changes in the esophageal mucosa that are part of an inflammatory response that has been increasingly investigated. Objective: To describe the histopathological findings from biopsies of pediatric and adolescent patients with EoE and to compare them with those from patients with clinical symptoms of epigastralgia. Material and methods: The results of esophageal cultures from biopsies were analyzed, seventeen with EoE diagnosis and seventeen with epigastralgia. The histopathological and immunohistochemical aspects, such as maximum number of eosinophils, papillary elongation, basal cell hyperplasia, dilatation of intercellular spaces, microabscesses, and CD1a expression were analyzed. Results: Among the histopathological findings, papillary elongation and basal cell layer hyperplasia were observed in all participants with EoE and in any of the sample of the epigastralgia group. Dilated intercellular space was found in all patients with EoE and in 29.41% of patients with epigastralgia. Conclusions: The amount of eosinophils may not by itself show the complexity of EoE. Future studies should be carried out in order to determine if any morphological findings may help in the differential diagnosis between EoE and proton-pump inhibitor-responsive esophageal eosinophilia, and whether they could be used to monitor the effectiveness of the EoE treatment.